2022
DOI: 10.1021/acsami.2c06841
|View full text |Cite
|
Sign up to set email alerts
|

Covalent Organic Framework Based on Azacalix[4]arene for the Efficient Capture of Dialysis Waste Products

Abstract: Azacalix[n]arenes (ACAs) are lesser-known cousins of calix [n]arenes that contain nitrogen bridges instead of methylene bridges, so they generally have higher flexibility due to enlarged cavities. Herein, we report a highly substituted cationic azacalix[4]arene-based covalent organic framework (ACA-COF) synthesized by the Zincke reaction under microwave irradiation. The current work is a rare example of a synthetic strategy that utilizes the chemical functionalization of an organic macrocycle to constrain its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…Azacalix [4]arene, an analog of calix[n]arenes, is conformationally flexible in solution due to its enlarged cavities. Skorjanc et al [92] constructed COFs from azacalix [4]arene and Zincke salt, which showed 2D topology composed of highly substituted 3D building blocks (Figure 13d). The terminal amino groups connected with the bipyridium units determines framework extension, which shows wavelike square structure caused by the macrocyclic nature of the azacalix [4]arene (Figure 13e).…”
Section: Chelating Macrocycle-attached Cofs For Adsorptionmentioning
confidence: 99%
See 3 more Smart Citations
“…Azacalix [4]arene, an analog of calix[n]arenes, is conformationally flexible in solution due to its enlarged cavities. Skorjanc et al [92] constructed COFs from azacalix [4]arene and Zincke salt, which showed 2D topology composed of highly substituted 3D building blocks (Figure 13d). The terminal amino groups connected with the bipyridium units determines framework extension, which shows wavelike square structure caused by the macrocyclic nature of the azacalix [4]arene (Figure 13e).…”
Section: Chelating Macrocycle-attached Cofs For Adsorptionmentioning
confidence: 99%
“…d) Schematic of azacalix [4]arene COFs. [92] e) structural models of the azacalix [4]arene COFs. f) Pseudo-second-order fitting and adsorption isotherm of uric acid and creatinine by the azacalix [4]arene COFs.…”
Section: Chelating Macrocycle-attached Cofs For Adsorptionmentioning
confidence: 99%
See 2 more Smart Citations
“…The capture of dialysis waste products is another use. The material combines a bispyridinium salt (BDB) with an azacalix [ 4 ] arene (ACA) following the Zincke reaction under irradiation of microwave materials at 90 °C for 3 h to generate the cationic ACA-COF [ 57 ]. Another ACA-COF was synthesized in solvothermal conditions, and the crystallinity observed was higher using microwave irradiation.…”
Section: Microwave-assisted Synthesis Of Cofsmentioning
confidence: 99%